(untitled) (Ciencias de la Ingeniería y Aplicadas, 2022)
Industrial process optimization aims to eliminate everything that does not add value to products and customer satisfaction. The metalworking industry in Ecuador represents 14% of GDP and has maintained an average annual growth of 7% since 2000. The objective of this study focused on the application of the lean manufacturing tool SMED in order to optimize the production process of industrial machinery and equipment in a metalworking company. The information obtained with the process flow diagram and the time study carried out showed high production cycle times, waits and delays in the conveyor belt manufacturing process; The sequence of operations of the process under study is manufacturing of the drive axle, manufacturing of the driving axle, CNC process, manufacturing of coils, turning of coils, cutting of rollers, manufacturing of plates for trough, manufacturing of fixed conveyor belt, process painting, electrical panel assembly and final machine assembly, corresponding to the manufacture of the conveyor belt machine; where the existence of activities that are not correctly distributed and controlled and that do not add value to the process was confirmed, which causes stoppages in machinery and an unbalanced process. Internal activities were converted into external ones, this represents for the company a reduction of 12.84% of its standard time and an increase in its productivity of 14.7%.